A description of the current status of chronic fatigue syndrome and associated factors among university students in Wuhan, China - Luo, Lunbing; Zhang, Yutong; Huang, Tao; Zhou, Fang; Xiong, Change; Liu, Yang; Zhai, Piyong; Wang, Guiping; Tan, Jianhua; Jiao, Chengjun; Chen, Xin; Yu, Jiao; et al. (Frontiers in Psychiatry, 2023)
Introduction Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a group of chronic conscious fatigue that is not easily relieved by rest and is accompanied by corresponding physiological dysfunction and psychological symptoms. However, due to the insufficient understanding of the pathogenesis of ME/CFS, there is currently a lack of effective treatment methods. In addition, there are few surveys on the current status of ME/CFS in the central region of China, and the data on ME/CFS among university students in the central region are lacking. This group conducted a survey on university students in Wuhan, Hubei Province in 2022 to collect and analyze the current status of ME/CFS among university students in central China for the first time, aiming to understand the current development of ME/CFS among university students, investigate the influencing factors of its prevalence, fill the data gaps, and provide a reliable basis for developing interventions for chronic fatigue syndrome among university students. Methods A cross-sectional study was conducted among university students in a university in Hubei province. Data were collected via online questionnaire surveys. The contents included demographic characteristics, lifestyles, disease history, depression, anxiety, sleep, ME/CFS and other associated factors. SAS 9.4 statistical software was used to analyze and estimate the effect of associated factors on ME/CFS. Results A total of 1826 subjects were included in the final analysis. The results showed that the prevalence of ME/CFS in university students was 6.25%. Univariate analysis showed that exercise, alcohol consumption, study, overnights, diet, anxiety, depression, and sleep quality were associated with ME/CFS (P < 0.05). Multivariate analysis showed that overnights, overeating, anxiety, and sleep quality were independent risk factors, while learning was a protective factor. Conclusion College students should pay enough attention to ME/CFS, improve their understanding of ME/CFS, and improve people’s ability to understand ME/CFS.